Getting by: The ethnomethods of everyday cycling navigation. (6th August 2020) - Lloyd, Michael
Abstract: Cycling is often carried out in public places, meaning that it is easy to both observe and video‐record cycling in action. Within sociology, ethnomethodology focuses on practical activities, often by collecting and analysing video data. Geographers have also used video data in researching cycling, but the two perspectives have little crossover. This article showcases an ethnomethodological analysis of video data on everyday cycling navigation, presenting three empirical examples. We see that cycling, accomplished by real interacting people, needs analysing in fine detail. Further knowledge of the mundane aspects of cycling mobility can usefully build upon such a videographic approach.